Parallel contagion phenomenon of concordant mental disorders among married couples: a nationwide cohort study. Issue 7 (20th February 2017) - Wang, Jong-Yi; Hsieh, Ming-Hong; Lin, Pei-Ching; Liu, Chiu-Shong; Chen, Jen-De
Abstract : Background: The aggregation of mental disorders in couples, as reported by prior research, indicates the effect of familial environments and warrants attention. However, the concordant categories of mental disorders in couples remain unclear. This study investigated spousal concordance for the category of mental disorders among couples throughout Taiwan by using factors associated with such disorders. Methods: 5643 couples in the 2002–2013 Taiwan National Health Insurance Research Database were analysed and compared with propensity-matched 5643 non-couples. Twelve independent variables, including spouse and shared characteristics, and the category of mental disorders were analysed, mainly by using multinomial logistic regression. Results: The determined prevalence rates for concordant categories of mental disorder were 0.19% for affective disorders, 6.96% for anxiety disorders, and 3.15% of other mental disorders. Multinomial logistic regression results revealed that two spouses were significantly more likely to be diagnosed with the same category of the aforementioned mental disorders (ORs=2.914, 1.776 and 1.727, respectively). Other associated factors included gender, age, occupation, comorbidity and region. The odds of concordances were significantly higher in couples than in non-couples. Conclusions: A category of mental disorder in one spouse is a determinant of that in the other spouse. This study extended the emotional contagion theory to the phenomenon of parallel contagion to reflect the three concordances, suggesting a direction of family-based mental health intervention, particularly prevention for the same category of mental disorders in couples. Policymakers should strengthen the coping strategies of the caring spouse and external support system to psychiatrically vulnerable families.